Growth and carcass production responses of EPMp broiler ducks to various levels of crude fiber and protein in the diet - Maijon Purba; L. Hardi Prasetyo (Indonesian Center for Animal Research and Development (ICARD), 2014)
Inclusion of crude fiber in diet is important for duck growth, but there is a limit in its use in order for the ducks to grow normally. The purpose of this study was to evaluate growth and carcass production responses of EPMp broiler ducks under different levels of crude fiber and protein in diets. Four hundreds and twenty day old ducklings were allocated into 7 treatments with 6 replications and each replication consisted of 10 ducks. The treatments were the factorial combinations of crude fiber content of 6 or 9% and protein content of 19, 21, or 23%; and BR-1 (starter diet) as positive control. The variables observed were: feed intake, weekly body weight, and percentage of carcass production. The results showed that all variables observed were not significantly affected by CF content, but highly significantly affected by crude protein levels in diet. Protein content of 19 or 21% in diet resulted in a better performance for EPMp ducks. The inclusion of high CF in diet did not affect carcass percentage, except for reduced abdominal fat. The study implies that administration of high CF (6 or 9%) with a protein content of 19 or 21% in the diet are still acceptable to EPMp ducks at 12 weeks